Subcutaneous foslevodopa in akinetic crisis. A case report from the neurological intensive care unit - Loeffler, Moritz A.; Mengel, Annerose; Single, Constanze; Weiss, Daniel; Feil, Katharina (Frontiers in Medicine, 2024)
Introduction Akinetic crisis is a severe deterioration of motor performance occurring in syndromes with pre- or postsynaptic dopaminergic deficit, necessitating effective dopamine replacement therapy. The subcutaneously applicable levodopa derivative foslevodopa represents a new therapeutic option for patients with advanced Parkinson’s disease as a continuous therapy. However, its potential role as a parenteral treatment option for akinetic crisis has not been investigated, yet. The case A 78 year-old patient who had developed akinetic-rigid symptomatology in the context of normal pressure hydrocephalus was admitted to our intensive care unit after experiencing an acute exacerbation of akinesia in the context of pulmonary infection. Off-label administration of subcutaneous foslevodopa was initiated after repeated failures to insert a gastric tube for enteral application of levodopa and contraindications against amantadine and apomorphine. Results Following the administration of a subcutaneous test dose, continuous application of foslevodopa via a B. Braun syringe pump was gradually increased to 0.3 mL/h during the daytime and 0.15 mL/h at night, corresponding to a levodopa equivalent dosage of 1,020 mg/d. This was accompanied by an improvement of the MDS-UPDRS III score from 85 points to 59 points after 72 h. Discussion Treatment of an akinetic crisis with subcutaneous foslevodopa in an intensive care unit setting has proven to be safe and effective in a patient with acute akinesia associated with dopamine-sensitive hydrocephalus. Due to the pathophysiological distinction from Parkinson’s disease, there may be differences in therapeutic response and side effects. Nevertheless, the method used here can serve as a protocol basis for the treatment of akinetic crises with foslevodopa in general and as a starting point for further research.